A Carboxymethyl Chitosan‐Based Double‐Crosslinking Hydrogel with Enhanced Antibacterial Properties for Accelerated Wound Healing. Issue 8 (16th August 2022) - Mo, Xinya; Huang, Wen‐Can; Sun, Shifeng; Chi, Zhe; Ding, Yuanyuan; Mao, Xiangzhao
Abstract : Front Cover : In article 2200060 by Wen‐Can Huang, Xiangzhao Mao, and co‐workers, a carboxymethyl chitosan‐based double‐crosslinking hydrogel dressing for accelerated wound healing is developed. In vitro and in vivo experiments demonstrate that the hydrogel has stretchability, tissue adhesion, antimicrobial functions, and exhibits excellent cytocompatibility and hemocompatibility. This hydrogel is anticipated to be widely used in bacteriaassociated wound management.